ҚАРАҚАЛПАҚ ЕРТЕКЛЕРИНДЕГИ ЗООНИМЛЕР - Искендерова, Е.К. (SCIENCE and SOCIETY, 2024)
The article is talked about Karakalpak tales and zoonyms. It is said that the zoonyms in fairy tales serve as similes, metaphors, and euphemisms. The place of zoonyms in human life is established by comparison with animals and examples.